1978
DOI: 10.1104/pp.62.6.889
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High Cation Concentrations on Photosystem II Activities

Abstract: The effects of wide concentration ranges of NaCI, KC, and MgCl2 on femcyanide reduction and the fluorescence induction curve of isolated spinach (Spinacia oleraces) chloroplasts were investigated. Concentrations of the monovalent salts above 100 mM and MgC12 above 25 mm produced a decrease in the rate of ferricyanide reduction by thylakoids uncoupled with 2.5 mm NH4Cl which cannot be attributed to changes in the primary photochemical capacity of photosystem IL Salt-induced decreases in the effective concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

1980
1980
1987
1987

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 15 publications
2
9
1
Order By: Relevance
“…Mills and Barber [22] have called it the 'irreversible quenching' and Baker [1] noted that it is also present in uncoupled chloroplasts; he stated that effects of high cation concentrations are not principally attributable to phosphorylation, since coupled and uncoupled chloroplasts exhibit similar activities, as we have also found [ Figure 4]. Numerous authors, such as Krause [16], have shown an Mg +÷ efflux from thylakoid related to light-dependent proton pumping.…”
Section: Correlated Influence O F Cation Concentration and Excitationsupporting
confidence: 74%
See 3 more Smart Citations
“…Mills and Barber [22] have called it the 'irreversible quenching' and Baker [1] noted that it is also present in uncoupled chloroplasts; he stated that effects of high cation concentrations are not principally attributable to phosphorylation, since coupled and uncoupled chloroplasts exhibit similar activities, as we have also found [ Figure 4]. Numerous authors, such as Krause [16], have shown an Mg +÷ efflux from thylakoid related to light-dependent proton pumping.…”
Section: Correlated Influence O F Cation Concentration and Excitationsupporting
confidence: 74%
“…However, even in saturating light conditions, DCIPr is significantly increased by low concentrations of Mg +÷, although to a much lesser extent, as already noted by Bose and Arntzen [3]. Baker [1] observed an increase in DCIPr at up to 25 mM of Mg +÷ in saturating light.…”
Section: Correlated Influence O F Cation Concentration and Excitationmentioning
confidence: 52%
See 2 more Smart Citations
“…This could result from a partial block in electron transfer after PSII, but stimulation of PSII activity could be a contributing cause. In isolated chloroplasts, the photoreduction of ferricyanide is stimulated progressively with increasing concentrations of NaCl up to 30 to 50 mm (2,24), an effect possibly related to a cation-dependent alteration in membrane ultrastructure that changes the distribution of absorbed light energy in favor of PSII at the expense of PSI (3). Since PSII is the rate-limiting photosystem at nonsaturating light intensities, it is interesting to speculate whether the enhanced growth of sugar beet in the presence of salt is related to an increase in the production of photosynthate.…”
Section: Discussionmentioning
confidence: 99%